Trichoderma : Ganoderma disease control in oil palm : a manual /: Ganoderma disease control in oil palm : a manual. (2019) - Virdiana, Ike; Rahmaningsih, Miranti; Forster, Brian P; Schmoll, Monika; Flood, J (Julie)
No abstract available